Entrepreneurs and digital workforce - Ahmad Fadzil, Muhammad Faisal; Kamaruddin, Kardina (Universiti Teknologi MARA, Terengganu, 2021)
During this pandemic era., entrepreneurs are one of the people that being effected by the pandemic and it effect their income too. One of the strategies to overcome this issue by learning on digital workforce. What is digital workforce? The digital workforce is a term recently coined to describe a range of robotic and automated technologies to improve employee productivity and efficiencies. Although many companies have adopted and implemented automated technologies, many innovations are still at the early stages. However, the paces of change are rapid, and the transitions are wide-ranging from big to small organizations and from old to new entrepreneurs. Digital Transition is best described as technological fusion, blurring the lines between the two areas of physics, digital, and biology. This rapid pace of change means that whole industries and organizations have a rapidly narrowing window of opportunity for future-readiness. Digital Workforce and advances in HR Technologies such as communications, combined with lifestyle trends, point to a future workforce that is more productive and more capable than ever before.